2015
DOI: 10.1016/j.bbmt.2015.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Blautia Is Associated with Reduced Death from Graft-versus-Host Disease

Abstract: The relationship between intestinal microbiota composition and acute graft-versus-host disease (GVHD) after allogeneic blood/marrow transplantation (allo BMT) is not well understood. Intestinal bacteria have long been thought to contribute to GVHD pathophysiology, but recent animal studies in non-transplant settings have found that anti-inflammatory effects are mediated by certain subpopulations of intestinal commensals. Hypothesizing that a more nuanced relationship may exist between the intestinal bacteria a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
557
6
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 626 publications
(583 citation statements)
references
References 54 publications
18
557
6
2
Order By: Relevance
“…Therefore, we conclude that the depletion of Collinsella may be highly specific to HF. Moreover, recent research demonstrated that Blautia might be associated with anti‐inflammatory mechanisms, as its intestinal abundance is associated with reduced death and improved overall survival in Graft‐versus‐Host‐Disease 36. Furthermore, a reduction in the butyrate‐producing genus Faecalibacterium is observed in HF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we conclude that the depletion of Collinsella may be highly specific to HF. Moreover, recent research demonstrated that Blautia might be associated with anti‐inflammatory mechanisms, as its intestinal abundance is associated with reduced death and improved overall survival in Graft‐versus‐Host‐Disease 36. Furthermore, a reduction in the butyrate‐producing genus Faecalibacterium is observed in HF patients.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] More recently, studies have found that microbiota injury frequently precedes severe GVHD, raising the possibility that loss of protective commensal bacteria during the course of the transplant may contribute to the development of GVHD pathophysiology. [5][6][7] Clinical strategies to intervene when microbiota injury occurs are being developed. To identify high-risk patients who could benefit most, a quick method for determining the "health" of an individual's microbiota would be an invaluable tool.…”
mentioning
confidence: 99%
“…15 Subsequently, the same group demonstrated the impact of recipient intestinal flora with high diversity and the abundance of the genus of Blautia as two independent protecting factors for aGVHD. 16 More recently, Soho et al reported in a single-center retrospective study, an increased GVHD related mortality associated to broad spectrum ATB used following aHSCT in adults. Feces composition of patients treated post-aHSCT with piperacillintazobactam was associated with a greater loss of diversity and most notably loss of Bacteroidetes and Lactobacillus.…”
Section: Discussionmentioning
confidence: 99%
“…This increased mortality appeared to be related to an increased risk of infections and of more severe aGVHD. 15,16 Furthermore, in aHSCT, delayed lymphopenia is considered to be one of the key factors which predict the incidence of aGVHD. 17,18 However, it remains unknown if lymphocyte recovery is influenced by the changes in the composition of the microbiota that are caused by prophylactic ATB treatment.…”
Section: Introductionmentioning
confidence: 99%